2020
DOI: 10.1002/jlcr.3823
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis and preliminary evaluation of an18F‐labeled tubastatin A analog for PET imaging of histone deacetylase 6

Abstract: Histone deacetylase 6 (HDAC6) is a unique member of the HDAC family because of its characteristics, namely, its cytoplasmic localization and ubiquitin binding. HDAC6 has been implicated in cancer metastasis and neurodegeneration. In the present study, we performed radiosynthesis and biological evaluation of a fluorine-18-labeled ligand [ 18 F]3, which is an analog of the HDAC6-selective inhibitor tubastatin A, for positron emission tomography (PET) imaging. [ 18 F]3 was synthesized by a two-step reaction compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The brain radioactivity level also peaked (7.86 ± 0.50% ID/g) at 10 min p.i., followed by a gradual decrease. The brain/blood radioactivity ratio remained stable at approximately 1.7 over a 60 min period; this ratio was much higher than that of an 18 F-labeled tubastatin A analogue (0.08–0.40; ≤ 0.55% ID/g in mouse brain) . High radioactivity uptake was observed in the liver and kidney, and this uptake was >20% ID/g at 60 min p.i.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The brain radioactivity level also peaked (7.86 ± 0.50% ID/g) at 10 min p.i., followed by a gradual decrease. The brain/blood radioactivity ratio remained stable at approximately 1.7 over a 60 min period; this ratio was much higher than that of an 18 F-labeled tubastatin A analogue (0.08–0.40; ≤ 0.55% ID/g in mouse brain) . High radioactivity uptake was observed in the liver and kidney, and this uptake was >20% ID/g at 60 min p.i.…”
Section: Resultsmentioning
confidence: 77%
“…Noninvasive imaging of HDACs by positron emission tomography (PET) is considered useful for detecting abnormalities in HDAC expression levels and assessing target engagement by HDAC inhibitors. , A number of HDAC radioligands for PET imaging have been developed to date; however, designing hydroxamic acid-based HDAC radioligands exhibiting good brain penetration is challenging due to their tendency to readily ionize . Adamantyl group-conjugated hydroxamic acids are exceptional examples of HDAC radioligands that can enter the brain. , One adamantyl group-conjugated HDAC radioligand, [ 11 C]­Martinostat, which visualizes primarily class I HDACs (HDAC1, 2, and 3), has already been used in clinical studies. , Regarding the development of HDAC6-selective PET ligands, radiosynthesis of tubastatin A, an HDAC6-selective inhibitor, and its analogues labeled with carbon-11 or fluorine-18 has been reported, but pharmacokinetic studies of these radioligands in mice demonstrated poor brain penetration. In 2017, Strebl et al reported the adamantyl group-conjugated HDAC6-selective radioligand [ 18 F]­Bavarostat (also known as [ 18 F]­EKZ-001), and brain penetration of this compound was demonstrated by PET imaging in rodents and nonhuman primates. , A first-in-human study of [ 18 F]­Bavarostat investigating the compound’s dosimetry, kinetic modeling in the brain, and sex differences was recently reported …”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Tago et al used an HDAC6-selective inhibitor, Tubastatin A 75 ( Figure 26 ), as the target-binding component for the synthesis of a 18 F-labeled PET agent [ 106 ]. An inhibition assay with non-radiolabeled 76 in HDAC1 and HDAC6 gave IC 50 values of 996 and 33.1 nM, respectively, demonstrating selectivity for HDAC6.…”
Section: Imaging Probesmentioning
confidence: 99%
“…It would be very interesting to investigate HDAC distribution over the spinal cord or in other tissues of patients. The recently developed HDAC6‐selective PET radiotracer [ 18 F]EKZ‐001 ([ 18 F]Bavarostat), the [ 18 F]‐ and [ 11 C]Tubastatin‐derived PET radiotracers, and the class IIa HDAC‐selective radiotracer [ 18 F]TFAHA might provide excellent tools to study HDACs selectively in different diseases (Celen et al, 2020; Laws et al, 2019; Lu et al, 2016; Strebl et al, 2017; Tago, Toyohara, & Ishii, 2020; Vermeulen, Ahamed, Luyten, & Bormans, 2019). Of particular interest for future research is the just recently published study by Koole and colleagues, investigating tolerability in a first‐in‐man study of [ 18 F]EKZ‐001.…”
Section: Imaging Studies Of Hdacsmentioning
confidence: 99%
“…Research based on ALS subtype could be an intriguing approach for further studies, as HDAC levels may vary depending on the mutation and thus associated pathways. Furthermore, the authors did not investigate mRNA differences in spinal cord, in which differences in HDAC levels were previously shown (Janssen et al, 2010 (Celen et al, 2020;Laws et al, 2019;Lu et al, 2016;Strebl et al, 2017;Tago, Toyohara, & Ishii, 2020;Vermeulen, Ahamed, Luyten, & Bormans, 2019). Of particular interest for future research is the just recently published study by Koole and colleagues, investigating tolerability in a first-inman study of [ 18 F]EKZ-001.…”
Section: Imaging Studies Of Hdacsmentioning
confidence: 99%